(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
Assessment in higher education is undergoing a fundamental paradigm shift from a mechanism of measurement (assessment of learning) to an engine of cognitive development and professional readiness (assessment for and as learning). This paper systematically analyzes the theoretical frameworks guiding modern educational evaluation, evaluates the systemic tension between traditional summative psychometrics and contemporary formative models, and investigates the impact of digital transformation, cloud analytics, and generative Artificial Intelligence (AI) on institutional evaluation ecologies. Through a structural synthesis of international pedagogical standards, this study proposes an integrated, multi-dimensional framework designed to maximize assessment validity, minimize institutional “silo effects”, and secure academic integrity in an era of ubiquitous automation.